2016
DOI: 10.1083/jcb.201508081
|View full text |Cite|
|
Sign up to set email alerts
|

Fat2 acts through the WAVE regulatory complex to drive collective cell migration during tissue rotation

Abstract: The atypical cadherin Fat2 binds the WAVE regulatory complex (WRC) and acts with receptor tyrosine phosphatase Dlar through the WRC to control collective cell migration during Drosophila oogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 34 publications
8
89
0
Order By: Relevance
“…We have not excluded an additional role in actin regulation other than polarized alignment; the requirement for Fat2 and actin but not MTs to maintain rotation, as well as the direct binding of actin regulators by vertebrate Fat1, a possible ortholog of Drosophila Fat2 (Moeller et al, 2004; Tanoue and Takeichi, 2004), suggests such a role. Moreover, while this work was in revision, Squarr et al (2016) showed that Fat2 can directly influence the actin cytoskeleton via binding to the WAVE complex.…”
Section: Discussionmentioning
confidence: 88%
“…We have not excluded an additional role in actin regulation other than polarized alignment; the requirement for Fat2 and actin but not MTs to maintain rotation, as well as the direct binding of actin regulators by vertebrate Fat1, a possible ortholog of Drosophila Fat2 (Moeller et al, 2004; Tanoue and Takeichi, 2004), suggests such a role. Moreover, while this work was in revision, Squarr et al (2016) showed that Fat2 can directly influence the actin cytoskeleton via binding to the WAVE complex.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, a WRC-interacting receptor sequence (WIRS) was identified in a number of membrane receptors that directly bind to the WRC components CYFIP1 and ABI1/ABI2 (Chen et al, 2014). Significantly, FAT2 (also known as Kugelei) contains such an element, and through this interaction, the WRC drives collective cell migration in Drosophila (Squarr et al, 2016).…”
Section: Jmymentioning
confidence: 99%
“…A recent paper proposed that dFat2 promotes follicle cell migration similarly to the way that the mammalian proteins function [28]. Although dFat2 lacks Ena/VASP binding sites in its ICD [15], it does have predicted binding sites for the Wave regulatory complex (WRC) [28,29], which helps to build the branched actin network found in lamellipodial protrusions.…”
Section: Introductionmentioning
confidence: 99%
“…Although dFat2 lacks Ena/VASP binding sites in its ICD [15], it does have predicted binding sites for the Wave regulatory complex (WRC) [28,29], which helps to build the branched actin network found in lamellipodial protrusions. Consistent with this observation, this paper showed that dFat2 is required for the formation of protrusions at the leading edge of each follicle cell, and that the WRC binds to dFat2’s ICD in vitro [28]. From these data and others, the authors concluded that dFat2 stimulates the formation of leading edge protrusions on a cell-autonomous basis by recruiting an actin assembly factor to its ICD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation